‘All Watched Over by Machines of Loving Grace? Information technology, in-person relationships and normative regulation in an ‘integral cooperative’ - Esteves, A. (Community Development Journal, 2022)
"On his study of the counterculture of the ‘60's and ’70's, Fred Turner argues that the application of systems-thinking and cybernetics to community-led initiatives (CLIs) makes them particularly vulnerable to internal factionalism and conflict, resulting from social and material pressures leading to the reproduction of mainstream norms and practices. Through the case study analysis of Cooperativa Integral Catalana (CIC) an “integral cooperative” for regional-level community development, this article explores how a governance strategy, combining online platforms for whole-system regulation and local nodes based on in-person relationships, promotes forms of normative regulation that contain factionalism and centrifugal tendencies in community-led initiatives (CLIs). Fieldwork evidence indicates that the use of online platforms and alternative currencies for overall network regulation does not prevent the accumulation of power by a core group of “professionalized activists”. The lack of processes of socialization aimed at building a common “habitus” among members of the cooperative with distinct identities, backgrounds and motivations creates difficulties to the development of relationships based on trust, as well as obstacles to the overall management of the cooperative. However, the in-person relationships of proximity build in regional-level nodes created “micro-public spheres” of praxis-based, co-constructed normative regulation that prevented the escalation of internal conflicts to reach a point of rupture. Such relationships provided a “cushion” of resilience that allowed CIC to begin, at the time of fieldwork, a process of decentralization and simplification of its structure."